ปัจจัยที่มีผลต่อการตัดสินใจเข้าร่วมเป็นเครือข่ายรถร่วม ในเขตอำเภอหนองแค จังหวัดสระบุรี - ศุภชีพ งามลาภ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The purpose of this study was to study the factors affecting the decision to join the truck network in Nongkae, Saraburi. The sample group was truck owners working in Nongkae, Saraburi. A total of 320 samples were randomized using a questionnaire as a data collection tool. The data were analyzed by descriptive statistics such as percentage, mean, standard deviation and inferential statistical analysis to test the hypothesis, including one-way analysis of variance and multiple regression analysis. The results showed that most of the respondents were in the age range of 40-50 years with average monthly transportation income of 50,000 - 100,000 baht, the current residence is the company s residence, and experience in truck driving is more than 10 years, the age of transportation vehicles is 10-15 years, and most of them are 4 wheeled vehicles. Different demographic factors in terms of age, monthly transportation income and the age of the transport vehicle affecting the decision to join the truck network is different and the factors affecting the decision to join the truck network in Nongkae, Saraburi in order from most to least is the income factor, welfare factor and reliability factor. The management factor of the organization and the security factor did not affect the decision level to join the truck network in Nongkae, Saraburi which could explain the influence was 47.7 percent correlation with significance at the 0.05 level.